A study of muslim perception towards unit trust in Kota Bharu / Siti Zubaidah Mat Nawi - Mat Nawi, Siti Zubaidah (Faculty of Business and Management, 2008)
Unit trust is a retail product designed to target small investors, salaried people and others who are intimidated by the mysteries of stock market but, nevertheless, like to reap the benefits of stock market investing. Due to that this study seeks to identify the factors that contribute to the in Kota Bharu. The factors which are the independent variable are service, performance and the nature of investment. Dependent variable is Muslim perception towards unit trust study case in Kota Bharu area. The objective of this study is to examine impact of each independent variable to its dependent variable as well as to conclude the relationships exist. The researcher used descriptive research design as it attempts to determine the perceptions of product or service characteristics. At the same time it also determines the degree to which variables are associated. In collecting the data, the researcher obtains from primary from questionnaires, interviews and observation while secondary data collected from journals, articles, books, reports and internet. Convenience sampling was used for this study as it allows obtaining a sample of convenient elements as well as accessible, easy to measure and cooperative. Due to that 100 respondents selected randomly to answer questionnaires which the researcher focused on Muslim in Kota Bharu area. Then the researcher analyzed the data from questionnaires using Statistical Package for Social Science 14.0 Students Version. Data was interpreted and test using frequency distribution analysis. Correlation analysis and simple regression used to test hypotheses. The results show that two out three independent variables have positive relationships with dependent variables. In terms of hypotheses testing, two hypotheses rejected null hypotheses. Recommendations outline by the researcher are to focus on customer awareness towards unit trust to change the Muslim perception the researcher lastly hope that further research will be done as it is meaningful to outline the hidden issues and factors that need to be focused by Muslim perception towards unit trust.